2014
DOI: 10.1117/12.2045630
|View full text |Cite
|
Sign up to set email alerts
|

Transillumination and reflectance probes forin vivonear-IR imaging of dental caries

Abstract: Previous studies have demonstrated the utility of near infrared (NIR) imaging for caries detection employing transillumination and reflectance imaging geometries. Three intra-oral NIR imaging probes were fabricated for the acquisition of in vivo, real time videos using a high definition InGaAs SWIR camera and near-IR broadband light sources. Two transillumination probes provide occlusal and interproximal images using 1300-nm light where water absorption is low and enamel manifests the highest transparency. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Occlusal transillumination images utilized light from a tungsten halogen source and bifurcated fiber optic bundle equipped with two linear arrays to impart light angled apically at the cementoenamel junction from both sides of the tooth and collect transmitted signal through a band pass 1300-nm optical filter and lens system. Detailed schematics covering the geometry of each modality and theory of the resulting image contrast can be found in previous publications [28]. NIR images were analyzed using the image analysis package provided by IgorPRO software (Wavemetrics, Lake Oswego, OR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Occlusal transillumination images utilized light from a tungsten halogen source and bifurcated fiber optic bundle equipped with two linear arrays to impart light angled apically at the cementoenamel junction from both sides of the tooth and collect transmitted signal through a band pass 1300-nm optical filter and lens system. Detailed schematics covering the geometry of each modality and theory of the resulting image contrast can be found in previous publications [28]. NIR images were analyzed using the image analysis package provided by IgorPRO software (Wavemetrics, Lake Oswego, OR).…”
Section: Methodsmentioning
confidence: 99%
“…When sound enamel becomes demineralized by caries, pores within the lesion grow to a similar size of the wavelength of light and act as Mie scatters increasing the scattering coefficient 2–3 orders of magnitude [27]. Differences in light scattering between sound and demineralized enamel can be detected by imaging light transmitted through or reflected back from the tooth [28]. Imaging with longer wavelength (λ≥1300-nm) NIR light also avoids the absorption bands of organic molecules responsible for pigmentation allowing direct imaging of decay beneath stained surfaces such as the occlusal grooves [29].…”
Section: Introductionmentioning
confidence: 99%
“…Occlusal transillumination images utilized light from a tungsten halogen source and bifurcated fiber optic bundle equipped with two linear arrays to impart light angled apically at the cementoenamel junction from both sides of the tooth and collect transmitted signal through a band pass 1300-nm optical filter and lens system. Detailed schematics covering the geometry of each modality and theory of the resulting image contrast can be found in previous publications [21, 22]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, near-infrared (NIR) imaging is currently being a new technology for trans-illumination and reflectance imaging of dental caries due to the high transparency of the enamel in the NIR light. 11 12 Usenik et al 13 showed that a near-infrared hyperspectral imaging system could distinguish the demineralization lesions from sound enamel within 156 seconds by imaging water evaporation dynamics.…”
Section: Introductionmentioning
confidence: 98%